Our Clinical Experiences in Pressure Sore in a period of 10 years - Ozturk, Ayse; Gurlek, Ali; Arslan, Ahmet; Firat, Cemal; Fariz, Alpay (Annals of Medical Research, 2021)
None
Keywords: Pressure sore, Surgical and conservative treatment, Rehabilitation.